Longitudinality and comprehensive care of children under one year old: assessment of caretakers - Braz, Janaina C.; Mello, Débora F. de; David, Yan GM; Teixeira, Simone A.; Prado, Aline Sousa; Furtado, Maria Cândida C. (Medicina (Ribeirao Preto), 2013)
Objective: This study aimed to evaluate the attributes longitudinality and comprehensive care in Family Health Units in Vitória da Conquista, Bahia, Brazil. Method: quantitative, cross-sectional study with data collected through the use of the Brazilian version of Primary Care Assessment Tool. This instrument covers the essential attributes of the Primary Health Care, including longitudinality and comprehensive care. We interviewed 271 caretakers of children under one year old who use the health facilities, from January to June 2012. Results: longitudinality scores were high (3.07±0.53), demonstrating good experience of caretakers regarding the actions derived from this attribute. On the other hand, the scores for comprehensive care related to available services and services provided were low (2.83±0.36 and 2.81±0.98). Such results demonstrate little awareness of caretakers related to available services, as well as services provided to children by health facilities. Conclusions: Family Health Strategy is a reference for most health needs of the child; it promotes the relationship between caretakers and health professionals, and enables the knowledge about children health status. However, despite the high coverage of the Family Health Strategy in the county, some children´s health actions are not experienced by caretakers. Managers and health professionals should have the priorities for child health in their agendas, as well as planning and implementation of actions which are related to the child health needs.